Legal Analysis of Immigration Detention Efforts in Immigration Criminal Enforcement - Muhammad Santiago Pawe; Syamsuddin Muchtar; Haeranah Haeranah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
This study aims to analyze the legal arrangements for immigration detention efforts in law enforcement of immigration crimes. This research was conducted using empirical research methods conducted in Makassar Immigration Office Class I TPI. Data collection techniques through interviews and literature studies. The data collected is processed and analyzed using qualitative analysis techniques and presented descriptively. The results of this study indicate that: Implementation of immigration detention efforts in law enforcement of immigration crimes is basically set on Law Number 6 of 2011 concerning Immigration, Government Regulation Number 31 of 2013 concerning Implementing Regulation of Law Number 6 of 2011 concerning Immigration and Regulation of the Minister of Law and Human Rights Number 39 of 2021 concerning Immigration Crime Investigation Procedures.